1985
DOI: 10.1159/000120251
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenomas in Pediatric Patients: Are They more Invasive?

Abstract: Twenty patients with biopsy proven pituitary adenomas that became symptomatic prior to the age of 20 years are reviewed. Based on age, the patients are divided into prepubertal, pubertal, and postpubertal groups. An increased incidence of invasiveness was observed in those patients with onset of symptoms during the pubertal years compared to patients whose symptoms first occurred during the postpubertal years. Other series of pediatric pituitary adenomas in the English literature are reviewed, and ostensibly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
1
7
0
1
Order By: Relevance
“…[5] Our study also shows no significant distribution according to sex (M:F = 1:1.2). In a study by Kanter et al, PAs show a predilection for females in the pediatric age group, [13] but in our study, we cannot encounter any pediatric patient. Rishi et al have shown a male predominance among NFPAs.…”
Section: Discussionmentioning
confidence: 64%
“…[5] Our study also shows no significant distribution according to sex (M:F = 1:1.2). In a study by Kanter et al, PAs show a predilection for females in the pediatric age group, [13] but in our study, we cannot encounter any pediatric patient. Rishi et al have shown a male predominance among NFPAs.…”
Section: Discussionmentioning
confidence: 64%
“…In the series by Kanter et al 16 an increased incidence of invasiveness was observed in adenomas where the onset of symptoms occurred during the pubertal years compared to those where symptoms first occurred during the postpubertal years. This has not been the experience in many other series.…”
Section: Discussionmentioning
confidence: 91%
“…Estos cambios degenerativos, necróticos y hemorrágicos de una parte del adenoma le darán aspecto quístico fácil de confundir con otras lesiones 15 . Algunos autores piensan que el prolactinoma en la edad pediátrica es más invasivo 16 ; sin embargo, otros no están de acuerdo 1,4,7,9 . Se ha publicado un caso maligno en un niño de 12 años con metástasis craneoespinales 16 meses después de la extirpación del tumor primario 17 .…”
Section: Discussionunclassified